Information Analytics in the Organizational Structure of Libraries of Top-Rated Universities in Ukraine - Kobelev, O. M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective. To study of the organizational information and analytical structures of libraries of top-rated universities in Ukraine, in particular, of 4 domestic universities that entered the World University Rankings 2019. Methods. The methodological basis of the study is the basic provisions of the general theory of social communications. Comparative analysis, sociocommunicative, information, adaptive and other approaches are used. Results. The form of organization of information and analytical activities in the library depends on its place in the library system and the existing organizational structure therein. There are two options for its organization. The first option involves the distribution of tasks between the existing library departments. The second one is the creation of an independent analytical unit in the organizational structure of the library. In the libraries of the universities under study, information and analytical functions are performed by other departments, primarily by the information and reference (bibliographic) units, information service as well as scientific and methodological (research) departments. Conclusions. Thus, information and analytical activity, even for scientific libraries of leading Ukrainian universities, remains primarily a tool for improving internal library processes, and not a separate product (service) that is purposefully produced and offered to readers. Meanwhile, the intensification of the use of information and analytical technologies in libraries, the creation of specialized units therein is one of the effective tools for optimizing library work.